Analysis of Factors Affecting Students' Grade Point Average (GPA) in Cirebon University Using Multiple Discriminant Analysis - Anna Febriana; Tantri Mariana; Kamsidin (MIREJ: Multidisciplinary Innovation Research Journal, 2025)
This research explores the factors that influence student academic achievement within the context of public and private universities located in Cirebon, Indonesia. The study employs discriminant analysis as its primary analytical method, utilizing primary data collected through questionnaires distributed to students across these institutions. The central aim is to identify and analyze the key determinants that significantly affect students' academic performance.The findings of the research highlight the significant impact of intelligence quotient (IQ) and study hours on student achievement. Furthermore, the analysis reveals that gender and university type (public or private) also play a role in differentiating levels of student achievement. These results contribute to a more nuanced understanding of the variables influencing academic success in the region. By employing discriminant analysis, the study effectively classifies students into distinct academic performance groups, specifically those with a GPA below 3.5 and those with a GPA of 3.5 or higher. This approach allows for the identification of factors that reliably distinguish between these groups. The outcomes of this research are intended to provide valuable insights for universities and educational stakeholders, enabling them to develop targeted strategies and support mechanisms to foster improved student outcomes and enhance the overall quality of higher education.